ナンキョク カイ ノ カキ パックアイス タイ ガイシュウイキ ニオケル カイチョウ ルイ ノ ブンプ - 内藤, 靖彦; ナイトウ, ヤスヒコ; 奈須, 敬二; ナス, ケイジ; 鈴木, 広志; スズキ, ヒロ; NAITO, Yasuhiko; NASU, Keiji; SUZUKI, Hiroshi (国立極地研究所, 1979)
P(論文) 海洋水産資源開発センターは毎年オキアミ調査を南極海で実施している.このオキアミ調査の一項として鳥類,海獣類の目視観察を実施している.本報告は1976-1977年,1977-1978年調査の結果である。調査区域は東経50°E～165°E,南緯62°S～68°S以内であった.出現種は12種であリ,卓越種群(アシナガコシジロウミツバメ等7種)は平均的に高い頻度でどの海域にも出現し,周極状分布が明瞭であった.非卓越種群(ハイイロアホウドリ等5種)は不均一分布を示し,周極状分布を示さなかった.卓越種群はススイロミズナギドリを除き,オキアミ補食者として知られている種であったが,非卓越種群はいずれもオキアミ補食者でなく,オキアミと海鳥分布の相関関係が推察された. The distribution of the Antarctic sea-birds was investigated in 1976-1977 and 1977-1978 summer seasons. The observations were performed along the outer margin of the pack ice area between longitude 50° E and 165° E. The investigated area was centered latitudinally between 62° S and 68° S. Twelve species observed in this area are divided into two groups, namely, rare species group and dominant species group. The species which rarely appeared, such as light-mantled sooty albatross, Antarctic petrel, sooty albatross, wandering albatross and Antarctic skua, are not krill-feeders. The latter group is composed of sooty shearwater, Wilson's storm petrel, snow petrel, Antarctic prion, giant petrel, cape pigeon and Antarctic petrel. These species showed the circumpolar distribution, and they are known to feed on the krill, except sooty shearwater. The relation between the sea-bird distribution and the krill was suggested. departmental bulletin paper